Three-dimensional assessment of the asymptomatic and post-stroke shoulder: intra-rater test–retest reliability and within-subject repeatability of the palpation and digitization approach. - Pain, Liza A. M.; Baker, Ross; Sohail, Qazi Zain; Richardson, Denyse; Zabjek, Karl; Mogk, Jeremy P. M.; Agur, Anne M. R. (Disability & Rehabilitation, 2019)
Purpose: Altered three-dimensional (3D) joint kinematics can contribute to shoulder pathology, including post-stroke shoulder pain. Reliable assessment methods enable comparative studies between asymptomatic shoulders of healthy subjects and painful shoulders of post-stroke subjects, and could inform treatment planning for post-stroke shoulder pain. The study purpose was to establish intra-rater test–retest reliability and within-subject repeatability of a palpation/digitization protocol, which assesses 3D clavicular/scapular/humeral rotations, in asymptomatic and painful post-stroke shoulders. Methods: Repeated measurements of 3D clavicular/scapular/humeral joint/segment rotations were obtained using palpation/digitization in 32 asymptomatic and six painful post-stroke shoulders during four reaching postures (rest/flexion/abduction/external rotation). Intra-class correlation coefficients (ICCs), standard error of the measurement and 95% confidence intervals were calculated. Results: All ICC values indicated high to very high test–retest reliability (≥0.70), with lower reliability for scapular anterior/posterior tilt during external rotation in asymptomatic subjects, and scapular medial/lateral rotation, humeral horizontal abduction/adduction and axial rotation during abduction in post-stroke subjects. All standard error of measurement values demonstrated within-subject repeatability error ≤5° for all clavicular/scapular/humeral joint/segment rotations (asymptomatic ≤3.75°; post-stroke ≤5.0°), except for humeral axial rotation (asymptomatic ≤5°; post-stroke ≤15°). Conclusions: This noninvasive, clinically feasible palpation/digitization protocol was reliable and repeatable in asymptomatic shoulders, and in a smaller sample of painful post-stroke shoulders. In the clinical setting, a reliable and repeatable noninvasive method for assessment of three-dimensional (3D) clavicular/scapular/humeral joint orientation and range of motion (ROM) is currently required. The established reliability and repeatability of this proposed palpation/digitization protocol will enable comparative 3D ROM studies between asymptomatic and post-stroke shoulders, which will further inform treatment planning. Intra-rater test–retest repeatability, which is measured by the standard error of the measure, indicates the range of error associated with a single test measure. Therefore, clinicians can use the standard error of the measure to determine the "true" differences between pre-treatment and post-treatment test scores.